Board Gender Diversity, Board Independence and Ownership Structure as Determinants of Corporate Social Responsibility Disclosure: Evidence from Indonesian Listed Banks - Zhou Siqi; Alin Nurlita (Universitas Muhammadiyah Purwokerto, 2026)
This study examines whether board gender diversity, the proportion of independent commissioners, public ownership and institutional ownership determine the extent of corporate social responsibility disclosure among Indonesian listed banks. Banking is a theoretically informative setting for this question: banks generate limited direct environmental impact yet transmit substantial social and environmental consequences through the projects they finance, and since the introduction of the sustainable finance framework they have faced explicit regulatory expectations of disclosure. The sample comprises 119 bank-year observations drawn from commercial banks listed on the Indonesia Stock Exchange over the 2021–2024 period, selected by purposive sampling. Corporate social responsibility disclosure is measured through a Global Reporting Initiative-based content-analysis index, and the hypotheses are tested using multiple linear regression. Board gender diversity is found to exert a positive and significant effect on disclosure, whereas institutional ownership exerts a significant negative effect. Neither the proportion of independent commissioners nor public ownership is significant. The model explains 26.8% of the variance in disclosure. The results indicate that the composition of the board influences disclosure through the resources and orientations directors bring to it, rather than through formal independence alone, and that concentrated institutional ownership may substitute for public disclosure rather than encourage it. The findings suggest that regulatory efforts to widen sustainability disclosure should attend to board composition and to the incentives of dominant institutional shareholders, not merely to the formal presence of independent commissioners.